Sistem Penilaian Penguji Sidang Proposal Pada PESSTA+ S2 di Universitas Raharja - Febriyanto, Erick; Handayani, Indri; Zebua, Vivid Kristiani Alfad (Technomedia Journal, 2019)
Assessment of examiners is very important in giving a decision to every leaners. Raharja University as one of univesity that has concentration in the field of computer science have various system to support academic activities , one of them is system PESSTA+S2. PESSTA+S2 ( Trial thesis evaluation plus postgraduate) is an information system which provides convenience to students as media to fulfill the evaluation point of proposal trial. The problem this now is assessment of examiners in the trial proposal really need precision and wary of examiners in inputting values of students cause still us Ms.Excel. The purpose of this research is to designing a system assessment of examiners in order to access by online on the system PESSTA+S2, so the system can be integrated by national. In solving existing problems,researcher use SWOT analysis system method and literature review. The result from this researcher is in the form system of assessment examiners proposal trial inside website PESSTA+S2 bassed Yii Framework that be convenience to inputting assessment of examiners at the Raharja University. Keywords : PESSTA+S2, assessment of examiners, The Trial Proposal, SWOT, Yii Framework